2019
DOI: 10.5380/raega.v46i3.67075
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Priority Areas for Forest Recovery Using Multicriteria Analysis in the Brazilian Atlantic Forest

Abstract: The collapse of a mining dam with 62 million cubic meters of mud in the Rio Doce basin resulted in the destruction of whole communities and large areas of Atlantic Forest. As forest restoration activities are among the most costly conservation strategies, prioritization of restoration efforts is crucial. In the present article, we mapped priority areas for forest recovery in a portion of the Rio Doce Basin (DO1) using a GIS-based (geographic information system) multicriteria decision analysis (MCDA) employing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 3 publications
(4 reference statements)
0
3
1
2
Order By: Relevance
“…This finding implies that forest patches would likely be larger when they are far away from the mine sites as compared to patches that are close to the mine sites. Whereas not directly related to the findings of this study, previous studies in forested landscapes in East Jaintia Hills-India, Brazilian Atlantic Forest and ridgetop biota of Appalachian forests have shown that reduced forest cover is mostly associated with mine sites [54][55][56] and thus, it is likely that forest patches are reduced or lost as a result of mining activities in such landscapes. Also, clearing of forest for mining activities would likely create room for other activities (e.g., road construction and human settlement development) and access to other parts of the forest cover.…”
Section: Discussioncontrasting
confidence: 71%
“…This finding implies that forest patches would likely be larger when they are far away from the mine sites as compared to patches that are close to the mine sites. Whereas not directly related to the findings of this study, previous studies in forested landscapes in East Jaintia Hills-India, Brazilian Atlantic Forest and ridgetop biota of Appalachian forests have shown that reduced forest cover is mostly associated with mine sites [54][55][56] and thus, it is likely that forest patches are reduced or lost as a result of mining activities in such landscapes. Also, clearing of forest for mining activities would likely create room for other activities (e.g., road construction and human settlement development) and access to other parts of the forest cover.…”
Section: Discussioncontrasting
confidence: 71%
“…However, there is only one program in the Plan, out of a total of 24, focused on this criterion: "Plan for the assessment, recovery, and monitoring of strategic areas for environmental conservation and preservation" (Sergipe, 2015). Valente et al (2017) and Almeida et al (2019) obtained the highest weight (0.87 and 0.51) for forest proximity to the drainage network. According to the authors, forested riparian areas are very important for forest restoration due to the connected fragments and improve water quality.…”
Section: Resultsmentioning
confidence: 91%
“…The weight assignment (comparison) process for each selected criterion was established considering the document analysis of the Basin diagnosis (Sergipe, 2015), the database available in Sergipe (2020), and the literature review on the importance of each criterion for sustainable development related to UN-based water resource management (2015). The authors of this study attributed the important values in the comparison matrix, drawing inspiration from Valente et al (2017) and Almeida et al (2019).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…A literatura apresenta inúmeros trabalhos conduzidos no âmbito da agricultura agroflorestal, manejo florestal e reflorestamento, visando beneficiar os recursos hídricos como, Randhir et al (2001), Bocher (2010, Ruiz (2015), Silva et al (2017), Almeida et al (2019), Mafra et al (2020). No Brasil e na América Latina, alguns projetos de Pagamento por Serviço Ambiental hídrico (PSA) ganharam destaque, tendo em vista a P a g e | 338 Revista Ibero-Americana de Ciências Ambientais v.12 -n.3  Mar 2021 conservação e restauração da cobertura vegetal como um critério para melhoria da qualidade e disponibilidade hídrica.…”
Section: Priorização De áReas Para Manejo Em Bacias Hidrográficasunclassified